Ecological scale and seasonal heterogeneity in the spatial behaviors of giant pandas. Issue 1 (January 2014) - ZHANG, Zejun; SHEPPARD, James K.; SWAISGOOD, Ronald R.; WANG, Guan; NIE, Yonggang; WEI, Wei; ZHAO, Naxun; WEI, Fuwen
Abstract We report on the first study to track the spatial behaviors of wild giant pandas (Ailuropoda melanoleuca) using high‐resolution global positioning system (GPS) telemetry. Between 2008 and 2009, 4 pandas (2 male and 2 female) were tracked in Foping Reserve, China for an average of 305 days (± 54.8 SE). Panda home ranges were larger than those of previous very high frequency tracking studies, with a bimodal distribution of space‐use and distinct winter and summer centers of activity. Home range sizes were larger in winter than in summer, although there was considerable individual variability. All tracked pandas exhibited individualistic, unoriented and multiphasic movement paths, with a high level of tortuosity within seasonal core habitats and directed, linear, large‐scale movements between habitats. Pandas moved from low elevation winter habitats to high elevation (>2000 m) summer habitats in May, when temperatures averaged 17.5 °C (± 0.3 SE), and these large‐scale movements took <1 month to complete. The peak in panda mean elevation occurred in Jul, after which they began slow, large‐scale movements back to winter habitats that were completed in Nov. An adult female panda made 2 longdistance movements during the mating season. Pandas remain close to rivers and streams during winter, possibly reflecting the elevated water requirements to digest their high‐fiber food. Panda movement path tortuosity and first‐passage‐time as a function of spatial scale indicated a mean peak in habitat search effort and patch use of approximately 700 m. Despite a high degree of spatial overlap between panda home ranges, particularly in winter, we detected neither avoidance nor attraction behavior between conspecifics.